Study to establish fiberoptic laryngoscopy as a diagnostic and investigation tool for laryngotracheal stenosis and to use the same for prognosis of the disease: retrospective analysis - Thenappan, T.; Vivekanandan, B.; Somu, L. (International Journal of Advances in Medicine, 2023)
Background: Laryngotracheal stenosis is a common benign condition of airway obstruction in both the pediatric and adult age group. This could either be acquired or congenital, in which there is narrowing of either the portions of the larynx or trachea making it difficult to breathe. This condition can be managed by several operative and endoscopic procedures. Flexible fiber optic laryngoscope is an excellent tool in the diagnostic investigation of laryngotracheal stenosis. Methods: This is a retrospective study that was done with data collected from the medical records department of patients diagnosed with laryngotracheal stenosis in a tertiary care hospital in the last 10 years. Results: A total of 22 patients who underwent FFL exam were taken for this retrospective study and the results were analyzed. Conclusions: This study proves that Fiberoptic laryngoscopy is a single modality diagnostic tool, which is useful in diagnosing, and localizing stenotic lesions in the Laryngotracheal region. It is cheap, less invasive and trained Otolaryngologist can perform this as an outpatient procedure. This therefore reduces the exposure to harmful radiation caused by repeated computed tomography scans.